Reprocessability of dynamic polydioxaborolane networks activated by heat, moisture and mechanical force. (17th November 2020) - Lei, Yufeng; Zhang, Anqiang; Lin, Yaling
Abstract: Covalent adaptive networks have shown great potential in sustainable crosslinked polymer materials. The incorporation of reversible covalent bonds also brings many possibilities for the material processing and recycling. Herein, we designed a polydioxaborolane network (PDOB) with abundant boronic-ester linkages. PDOBs showed tunable mechanical properties and viscoelasticity from highly stretchable elastomer to rigid thermoset by varying the composition. The dynamic dioxaborolane metathesis and reversible hydrolysis/rebinding of boronic-esters endowed PDOBs with remarkable reprocessability with the assistance of heat or moisture. Furthermore, the theoretical topology freezing transition temperature ( T v ) of PDOBs was calculated to be below their glass transition temperature ( T g ). We investigated the reprocessability of PDOBs at different temperature and found that PDOBs could be remolded at a temperature window between T v and T g even without the participation of water. The compressive force could break the reversible linkages into reactive sites, as well as promote exchange reactions, which subsequently facilitated interfacial integration. Graphical abstract: Image 1 Highlights: Polydioxaborolane networks were prepared via condensation from small-molecular diols and bornic-acids. Under- T g  reprocessability of polydioxaborolane network was activated by compression force without water. Reversible dioxaborolane chemistry was discussed as the structural cause of the unconventional reprocessability.